Fatigue life assessment of uni‐ and multidirectional carbon fiber reinforced plastics with regard to stiffness degradation: Lebensdaueranalyse von uni‐ und multidirektionalen kohlefaserverstärkten Kunststoffen unter Berücksichtigung von Steifigkeitsänderungen. Issue 3 (27th March 2018) - Rösch, P.; Bruder, T.; Wagner, P.
Abstract: Carbon fibre reinforced plastics are widely used in the automotive industry. In this paper a short introduction into the theoretical damage mechanisms and fatigue assessment approaches applicable for carbon fibre reinforced plastics is provided. The fatigue behaviour of uni‐ and multi‐directional carbon fibre laminates is shown for various laminate orientations and layups under axial loading. In addition to constant amplitude loading, experimental results using multiple staged block loading are presented. Online stiffness measurement during fatigue life is conducted. Supplementary investigations using in‐situ X‐ray and local strain measurements give further insight in the damage mechanisms. Furthermore a phenomenological residual stiffness approach is presented in order to describe the fatigue behaviour of the carbon fibre reinforced plastic tested in this project. Numerical evaluations are performed using Siemens Virtual.Lab Durability software and its composite fatigue solver. The computed stiffness degradation curves and corresponding fatigue life results are compared to the obtained test data under constant amplitude (SN curve and stiffness degradation) as well as multiple staged block loading.